Systematic Literature Review: Kemampuan Komunikasi Matematis Siswa Smp Kelas IX Dalam Pembelajaran Daring - Fitria Karomah; Heni Pujiastuti (Jurnal THEOREMS (The Original Research of Mathematics), 2023)
By developing students' mathematical communication skills during a pandemic, students can achieve learning success in the implementation of online learning. But in practice, students' mathematical communication skills are still not good. This study aims to review a number of research articles that are relevant to students' mathematical communication skills in online learning. This type of research is Systematic Literature Review or SLR. Data collection techniques are carried out by collecting a number of research articles available on Google Scholar. There were 10 journal articles used in this study. Based on the results of the study, it shows that in the implementation of online mathematics learning, mathematical communication skills in students are classified as low category. This is caused by two factors: 1) from within students, such as student learning motivation; 2) from outside students, such as less qualified learning resource facilities. The solution so that students' mathematical communication skills can improve is by creating innovative learning such as using interactive learning media.Keywords: Mathematical Communication Skill, Online Learning, Systematic Literature Review